Effect of kinetically altering a repetition via the use of chain resistance on velocity during the bench press - Baker, D. G.; Newton, R. U. (The Journal of Strength and Conditioning Research, 2009)
It is theorized that the force and velocity profile of a repetition performed during a standard barbell exercise may be altered by substituting suspended chains for some portion of the total resistance. The purpose of this study was to document the alterations in lifting velocity that occur when the bench press exercise is performed as standard (BP) or with the substitution of resistance via chains draped over the barbell (BP+CH). Thirteen professional rugby league players participated in this study as part of their usual training program. Each subject performed 2 sets of 3 repetitions under the following conditions: The BP+CH condition, where the barbell resistance of 60% 1RM (repetition maximum) was supplemented by 17.5-kg in chains draped over the barbell (total resistance was about 75% 1RM), and the BP condition, where the total resistance was the same but was constituted in the form of standard barbell weights. The BP+CH condition resulted in increases in mean and peak concentric lifting velocities of around 10% in both sets as compared to both BP sets. Eccentric peak velocities were more varied in response, but generally the addition of chain resistance could be said to allow for increased velocities. The result may be partially explained by the eccentric unloading that occurs as the chain links furl upon the floor in the latter stages of the eccentric range. This eccentric unloading precipitates a more rapid stretch-shorten cycle (SSC) transition and possibly a within-repetition postactivation potentiation (PAP) that allows the subject to utilize faster lifting velocities in the initial concentric portion, which flow through to the remainder of the concentric phase. Therefore the use of chains appears warranted when athletes need to lift heavy resistances explosively.